Long-Term Liver Expression of an Apolipoprotein A-I Mimetic Peptide Attenuates Interferon-Alpha-Induced Inflammation and Promotes Antiviral Activity - Fernandez-Sendin, Myriam; Di Trani, Claudia Augusta; Bella, Angela; Vasquez, Marcos; Ardaiz, Nuria; Gomar, Celia; Arrizabalaga, Leire; Ciordia, Sergio; Corrales, Fernando J.; Aranda, Fernando; Berraondo, Pedro (Frontiers in Immunology, 2021)
Apolipoprotein A-I mimetic peptides are amphipathic alpha-helix peptides that display similar functions to apolipoprotein A-I. Preclinical and clinical studies have demonstrated the safety and efficacy of apolipoprotein A-I mimetic peptides in multiple indications associated with inflammatory processes. In this study, we evaluated the effect of the long-term expression of L37pA in the liver by an adeno-associated virus (AAV-L37pA) on the expression of an adeno-associated virus encoding interferon-alpha (AAV-IFNα). Long-term IFNα expression in the liver leads to lethal hematological toxicity one month after AAV administration. Concomitant administration of AAV-L37pA prevented the lethal toxicity since the IFNα expression was reduced one month after AAV administration by decreasing the expression of IFNα. To identify the mechanism of action of L37pA, a genomic and proteomic analysis was performed fifteen days after AAV administration when a similar level of IFNα and interferon-stimulated genes were observed in mice treated with AAV-IFNα alone and in mice treated with AAV-IFNα and AAV-L37pA. The coexpression of the apolipoprotein A-I mimetic peptide L37pA with IFNα modulated the gene expression program of IFNα, inducing a significant reduction in inflammatory pathways affecting pathogen-associated molecular patterns receptor, dendritic cells, NK cells and Th1 immune response. The proteomic analysis confirmed the impact of the L37pA activity on several inflammatory pathways and indicated an activation of LXR/RXR and PPPARα/γ nuclear receptors. Thus, long-term expression of L37pA induces an anti-inflammatory effect in the liver that allows silencing of IFNα expression mediated by an adeno-associated virus.